Modelling the bandwidth allocation problem in mobile service-oriented networks - Gao, B; He, L; Chen, C (Association of Computing Machinery, 2015)
When the services requested by mobile application workflows are distributed over a network of mobile smart devices, the question arises as to which service should be allocated with how much bandwidth and when in order to satisfy service demands? Furthermore, the mobility of smart mobile devices brings forward the challenge to determine how changes in mobile network conditions affect the bandwidth requirements of interacting services. In this paper, we construct a Network I-O model to describe the bandwidth dependencies in mobile service-oriented networks incorporating and extend on the principles of the Leontief Input-Output model in economics. Various factors such as bandwidth and service demand are accounted for in the model. The network I-O model lays the foundation for future objective developments in ubiquitous mobile computing scenarios. Results from simulation studies are presented to demonstrate the effectiveness of the proposed methods.